Quantitation of mRNA species by RT-PCR on total mRNA population. - Hamoui, S; Benedetto, J P; Garret, M; Bonnet, J (Genome Research, 1994)
PCR is commonly used for mRNA quantitation. Previously described procedures are applied to one or a few specific mRNA sequences. We show here that methods used for amplifying heterogeneous cDNA populations can be applied to the quantitation of many mRNA species. This quantitation is achieved by dot blotting and hybridization with the corresponding probes after amplifying a bulk mRNA population. Only a single, two-round-amplification assay is required for quantitation of a whole set of mRNA species. The proportionality of input molecules to output signal was shown by performing a series of control experiments. We applied this technique to measure the relative variations of the MBP, Po, and MAG mRNA sequences in the normal trembler mouse model. The results were consistent with previously described Northern blot data. This quantitative PCR method provides a rapid and reliable way to quantify relative amounts of mRNA species in small amounts of total RNA by using internal controls.